(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Genderand the Politics of Modernity: The New Indian Woman in Four ContemporaryWomen’s Magazines Politically and methodologically, this assertiveparticipation of women in right wing campaigns, pulled many of our assumptionsinto a state of crisis for we have always seen women as victims of violencerather than its perpetrators and we have always perceived their public,political activity and interest as a positive, liberating force.1